Polydopamine-embedded Cu2−xSe nanoparticles as a sensitive biosensing platform through the coupling of nanometal surface energy transfer and photo-induced electron transfer1. Issue 12 (21st June 2015) - Zou, Hong Yan; Gao, Peng Fei; Gao, Ming Xuan; Huang, Cheng Zhi
<x xml:space="preserve">Abstract</x> This study innovatively highlights the mechanistic details of NSET and PET (NSET©PET) coupling processes, and the disclosed mechanism provides new opportunities for sensitive biosensing applications.